Effects of VEGF Inhibitor Conbercept on Corneal Neovascularization Following Penetrating Keratoplasty in Rabbit Model - Liu, Huan (Clin Ophthalmol, 2020)
PURPOSE: To evaluate the effects of the vascular endothelial growth factor inhibitor conbercept (KH902) on corneal neovascularization and wound healing following penetrating keratoplasty in rabbits. METHODS: Conbercept was administered to New Zealand white rabbits through topical and subconjunctival routes. Corneal neovascularization and wound healing were examined by slit-lamp photography and histological analyses. The expressions of vascular endothelial growth factor inhibitor, α-smooth muscle actin, and keratocan in the corneal grafts were measured by real-time quantitative polymerase chain reaction (RT-qPCR). RESULTS: The anterior segment photographs demonstrated that corneal neovascularization started in the 2nd week. In the 4th week, histologically, the superficial corneal stroma layer showed disordered arrangement, and there were large numbers of dense inflammatory cells and blood vessels in the stroma layer. Vascular endothelial growth factor in the experimental groups was significantly decreased at all time points compared with the control group (both P = 0.001). Expression of α-smooth muscle actin in corneal grafts demonstrated an increase in time even it was lower in experimental groups, but the difference was not statistically significant (P equaled to 0.507 and 0.723, respectively). There were no significant differences with the expression of keratocan in all groups except that it significantly declined at the 4th week as to the second week in all groups and P values were 0.022, 0.020 and 0.014 in control (C), topical (E1), and subconjunctival (E2) group, respectively. CONCLUSION: The study found that conbercept inhibited the formation of corneal neovascularization without affecting keratocan-mediated corneal wound healing and there were no significant differences between topical administration of different doses of conbercept on the rabbit corneal neovascularization after penetrating keratoplasty in this study.